Medication Reconciliation in Primary Care: Practices, Knowledge and Attitudes in the Lisbon and Tagus Valley Health Region - Ascenção, Raquel; Almeida, Mariana; Ribeiro, Cristina; Broeiro, Paula; Costa, João (Acta medica portuguesa, 2025)
Despite the importance of medication reconciliation for the continuity of care, there is currently no information on the practices, knowledge, and attitudes of Portuguese family doctors on this subject. This study aimed to characterize the formal medication reconciliation procedures in the Lisbon and Tagus Valley Health Region, as well as the perception of family doctors in this region about what they know, how they think and how they practice medication reconciliation. We conducted an observational, cross-sectional and descriptive study, using two observation units: primary health care units (study 1) and family doctors (study 2) in the Lisbon and Tagus Valley Health Region. Data was collected through two self-completed questionnaires, which were made available online. A total of 89 primary healthcare units and 208 family doctors participated in the study (31% and 12% response rates, respectively). Only one in four units (n = 22/89) had a formal medication reconciliation procedure. Among the units with a formal procedure, there was variability in some parameters, although all procedures included physicians. More than 70% (n = 150; 72.1%) of family physicians reported having previous contact with the term 'medication reconciliation', and a half (n = 104; 50.0%) reported carrying out medication reconciliation in more than 75% of consultations after hospital discharge. No differences were identified regarding the frequency with which family physicians practice medication reconciliation after hospital discharge depending on age, gender, type of unit where they work, and volume of consultations. Most family physicians (n = 155; 74.5%) included the three steps recommended by the Directorate-General for Health at the time and resolved discrepancies without contacting the hospital physician (n = 168; 88.8%). Family physicians recognize the importance of medication reconciliation (more than 95% agree/completely agree), although the level of agreement regarding their responsibility for this practice is lower. The proportion of primary health care units with a formal medication reconciliation procedure is low. Family doctors in the Lisbon and Tagus Valley Region value medication reconciliation, although they do not include it in all consultations after hospital admission. Communication between levels of care and the standardization of processes are areas with potential for improvement to promote the safe and patient-centered use of medication.